Case Report: Malignant PEComa of the thyroid combined with follicular carcinoma: a rare case of collision tumor - Liu, Yongchen; Lin, Yuanpei; Li, Xiaomei; Chen, Jian; Chen, Xinmei; Deng, Jiangbo; Wu, Zeyu (Frontiers in Oncology, 2026)
We present a rare case of a collision tumor comprising a malignant perivascular epithelioid cell tumor (PEComa) of the thyroid combined with a tiny invasive follicular carcinoma (FTC) in a 72-year-old female patient. The patient presented to the hospital with a painless anterior cervical mass discovered one month prior, and examination revealed a 50 mm × 30 mm mass in the left lobe of the thyroid gland. Ultrasound showed multiple solid and mixed lesions with gross calcifications in both thyroid lobes. The patient underwent total resection of the left thyroid and isthmus plus right subtotal resection. Histopathological examination revealed two distinct tumor components in the left lobe: immunohistochemistry revealed a PEComa component (HMB45+/SMA+/Desmin+, Ki-67 about 50%, P53 missense mutation) and a follicular carcinoma component (TTF-1+/PAX8+/TPO+, Ki-67 about 3% and P53 wild-type). The two components were well demarcated without mutual migration, meeting the diagnostic criteria for collision tumors. This case represents the first reported collision tumor combining thyroid PEComa and FTC, with immunohistochemistry confirming the independent origins of both tumors. The findings expand our understanding of thyroid tumor varieties and highlight the crucial role of Ultrasound and histopathology in diagnosing and managing complex thyroid tumors, serving as a valuable reference for similar cases.